Biochemical Alterations and Their Relationships with the Metabolic Syndrome Components in Canine Obesity - Tippayaporn Tribuddharatana; Yuwadee Kongpiromchean; Kosit Sribhen; Choosri Sribhen (Agriculture and Natural Resources, 2011)
Metabolic changes accompanying obesity have been intensively studied in humans but are rarely reported in animals. The present study aimed to investigate alterations of glucose metabolism and biochemical parameters in renal, lipid and liver profiles and to study their metabolic relationship determined in 31 obese dogs compared with 31 non-obese control dogs. The results showed that with the exception of creatinine and aspartate aminotransferase, all other parameters measured in obese animals exhibited significantly higher levels than those in the control group. In contrast to non-obese dogs, significant associations of glucose with several lipid parameters and liver enzymes alanine aminotransferase (ALT) and gamma-glutamyltransferase (GGT) were observed in obese dogs. These enzymes, on the other hand, displayed significant correlations with total cholesterol and low-density lipoprotein cholesterol, but not with high-density lipoprotein cholesterol. The results indicated that ALT and GGT may have major pathophysiological roles in obesity-related metabolic alterations and should be included as biochemical criteria of metabolic syndrome in canine obesity.